1972
DOI: 10.1111/j.1471-0528.1972.tb14179.x
|View full text |Cite
|
Sign up to set email alerts
|

Vectorcardiography and Acid‐base Balance in the Human Fetus

Abstract: Summary An analysis of the configuration of the fetal electrocardiogram assessed by recording the ratio of the positive and negative deflections of the QRS complex has been performed in relation to the QRS complex of the neonatal electrocardiogram. Changes in R/S ratios in the fetal electrocardiogram late in labour were significantly related to changes in Lead II of the neonatal electrocardiogram. On the basis of the method described by Larks (1965) the mean cardiac axis of the fetus early in labour was +144.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1973
1973
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Specifically, the P-R interval, the ratio of the amplitude of the T wave to that of the QRS complex (T/QRS), and the ratio of the amplitude of the R wave to that of the S wave (R/S) were calculated. The cardiac axis was calculated according to SYMONDS [15]. Short term heart rate variability, or the instantaneous variability is defined here as the average of the absolute value of the instantaneous heart rate difference over the given time period.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the P-R interval, the ratio of the amplitude of the T wave to that of the QRS complex (T/QRS), and the ratio of the amplitude of the R wave to that of the S wave (R/S) were calculated. The cardiac axis was calculated according to SYMONDS [15]. Short term heart rate variability, or the instantaneous variability is defined here as the average of the absolute value of the instantaneous heart rate difference over the given time period.…”
Section: Discussionmentioning
confidence: 99%
“…Current commercially available FSEs record the potential difference (which we interpret as the fetal ECG) between an electrode attached to the fetal scalp and a second electrode displaced by a few millimetres, in contact with the electrically conducting amniotic fluid, cervix or vagina. The fetal ECG from such a configuration in active labour has been reported as most closely resembling lead II of the neonatal ECG (Symonds 1972).…”
Section: Detecting the Fetal Ecgmentioning
confidence: 93%
“…The reference electrode is in contact with the cervix or vagina, either directly or via amniotic¯uid and the ECG recorded is most similar to lead II of the neonatal ECG. 59 This lead will record only T wave changes which occur in the horizontal plane of the heart. Experimental data showed that T wave changes were best detected by a lead III or AVF con®guration which is sensitive to changes in the longitudinal axis of the fetus.…”
Section: Ecg Monitoring Technologymentioning
confidence: 99%